The Impact of the Church Council’s Role in Improving Christian Religious Education at the Ina Parari Kamis HKBP Petra Church in Pematangsiantar Category - Sunggul Pasaribu; Ester Sitorus (CV Putra Publisher, 2026)
The role and duty of the congregation is to educate and teach God's Word to the ministry category of Women Thursday Society (Ina Parari Kamis) at HKBP Petra Pematangsiantar so that the member of the society can grow in faith and be active in any worship. As the duty of the church's call to the community in terms of fellowship, witness and service, the Word of God says [1]: